The Clinical Effectiveness of Platelet-Rich Fibrin in Post-Extraction Healing: A Systematic Review of Randomized Controlled Trials - Liene Janaite; Irina Vasilcenko; Ingrida Cema; Ieva Bagante (Medicina, 2026)
Background and Objectives: Platelet-rich fibrin (PRF) has been widely investigated as a biological material to enhance healing after tooth extraction; however, its clinical effectiveness remains uncertain. This systematic review evaluates the available evidence on its effectiveness in post-extraction socket management. Materials and Methods: A literature search was conducted across eight electronic databases for English-language studies published between 2015 and 2025. Only randomized controlled trials, including parallel-group randomized trials and randomized split-mouth trials, involving PRF with a control group were considered. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool (RoB 1). Due to substantial clinical heterogeneity in PRF preparation protocols, outcome measures, and follow-up periods, a narrative synthesis was performed instead of a meta-analysis. Results: A total of 174 records were identified, of which 9 studies met the inclusion criteria. The methodological quality of the studies included was evaluated to assess the risk of bias, in accordance with the recommendations of the Cochrane Handbook for Systematic Reviews of Interventions. Overall, 394 patients underwent 817 tooth extractions: 414 sockets were treated with different types of PRF, 251 were left to heal after suturing, and 143 were filled with a hemostatic sponge prior to suturing. Conclusions: PRF demonstrated superior outcomes in soft tissue healing and radiographic new bone density, although no statistically significant differences were observed in other parameters. Therefore, the available evidence does not allow us to draw definitive conclusions regarding the clinical effectiveness of PRF for socket filling after tooth extraction. The literature indicates that it may promote soft and hard tissue healing and reduce pain, swelling, and the risk of alveolar osteitis; however, evidence regarding its therapeutic effect on alveolar socket healing remains contradictory.